Comparison of Calcium Hydroxide, Chlorhexidine and Triple Antibiotic Paste As Intracanal Medicaments In Patients With Acute Periapical Infections - Syed Adeel Ahmed; Shama Asghar; Safia Anwar (Journal of Bahria University Medical and Dental College, 2019)
Objective: To compare the effects of calcium hydroxide, triple antibiotic paste (TAP) and chlorhexidine (CHX) as the intra-canal medicaments in post-operative pain reduction. Study Design and Setting: This was a Quasi experimental study conducted in Bahria University Medical and Dental College, Department of Operative Dentistry for the period of six months. Methodology: Patients with acute periapical infections in single rooted teeth were divided into 3 groups. Group 1 received Calcium hydroxide, group 2 received Chlorhexidine and group 3 received Triple antibiotic paste as intracanal medicament. Each group comprised of 30 patients therefore the total participants of the study were 90. Patients were recalled on 2nd, 7th and 15th day postoperatively and the pain was recorded by using Visual Analogue Scale. Results: Among the study participants; two patients receiving calcium hydroxide were pain free after 2 days and this number increased to 11patients after 7 days. From the CHX group; nine patients were pain free after two days and 23 patients reported no pain after 7 days. In TAP paste group 3 patients reported no pain after 2 days and 22 after 7 days. No patient reported pain after 15 days in any group. Data was statistically analyzed by using SPSS version 23 and Chi-square test was used for descriptive analysis. Conclusion: Intra-canal medicaments significantly reduced inter-appointment pain. The chlorhexidine and triple antibiotic paste were more effective as compared to calcium hydroxide.